Measuring Knowledge for Visual Basic's Student - Syed Hashim, Sharifah Nurhasnida (Universiti Teknologi Petronas, 2005)
Knowledge is so valuable and that's why it is significant to find a measurement in measuring the knowledge, so the value of knowledge been gain can be amounted and easy to describe. As much research been done in measuring knowledge field, especially the organization knowledge, this project objective is to find out student knowledge performance and activities through a forum in order to find what characteristics required in creating technique of measuring student knowledge for Visual Basic's student. In completing this project, the methodology that been used is quite similar to a Waterfall Model, but some part have been changes to suit the timeline and information been gather. The findings from this studyhighlight an appropriate metrics used to get result in measuring student knowledge in Visual Basic by using Brand Equity and Probability as indicators in measuring. The final result in this measuring technique is valued between 0 until 1.